0470 Pre-treatment Objective Short Sleep is Associated with Poor Treatment Response in Patients with Insomnia and Major Depression: A Report from the TRIAD Study. (25th May 2022) - Edinger, Jack; Eldridge-Smith, E Devon; Buysse, Daniel; Thase, Michael; Krystal, Andrew; Wisniewsk, Stephen; Manber, Rachel
Abstract: Introduction: Several studies have shown that patients with short sleep duration show a poor response to cognitive behavioral insomnia therapy insomnia (CBT-I) but such studies have not included patients with comorbid conditions. This study was conducted to determine whether pre-treatment sleep duration moderates the response of patients with major depression (MDD) and insomnia (ID) disorders to a combined CBT-I and antidepressant medication treatment. Methods: This study involved a secondary analysis of data from the TRIAD trial that tested combined CBT-I/antidepressant medication treatment of patients with MDD and ID. Participants (N=99; 70 women; Mage = 47.7 +/-12.4 yrs.) completed pre-treatment polysomnography (PSG) and were randomly assigned to a 12-week treatment comprised of antidepressant medication combined with CBT-I or a sham quasi-desensitization therapy for insomnia (DTI). Short and longer sleepers were defined using PSG total sleep time cutoffs of <5, <6 and <7 hours for short sleep. Insomnia and depression remission determined respectively from the Insomnia Severity Index and Hamilton Rating Scale for Depression were used to compare treatment responses of short and longer sleepers defined by the cutoffs mentioned. Results: Logistic regression analyses showed that statistically significant results were obtained only when the cutoff of <5 hours of sleep was used to define "short sleep." CBT-I recipients with > 5 hours of sleep were significantly more likely to achieve insomnia remission than were either the DTI recipients with > 5 hours of sleep (OR = 6.72; 95% CI = 2.03 – 22.26) or the CBT-I recipients with short sleep (OR = 18.92; 95% CI = 2.03 – 178.69). The longer sleeping CBT-I group was also more likely to achieve insomnia and/or depression remission than was either the longer sleeping DTI group (OR = 3.12 95% CI = 1.11 – 9.53) or the shorter sleeping CBT-I group (OR = 8.464; 95% CI = 1.40 – 51.12). Conclusion: Sleeping <5 hours may dispose patients with comorbid MDD/ID to a poor response to combined CBT-I/antidepressant medication treatments for their insomnia and depression. Future studies to replicate these findings and explore mechanisms of treatment response seem warranted. Support (If Any): National Institutes of Health, Grant Numbers MH078924, MH078961, MH079256 and HL096492.